ANALYSIS OF HOW PERSONAL DATA PROTECTION ACTB.E. 2562 (2019) REFLECTON CHINESE MESSAGING APPLICATION‟S PRIVACY POLICY - JUTACHAVAKUL, CHAMA (Chinese Language and Culture Journal, 2020)
In the digital century, it can be said that technology leads the way of consumer behaviour, markets, and product innovation. Consequently, most communication and trading happen on the electronic devices. The objectives and contributions of this study are to understand how the Personal Data Protection Act (“PDPA”) B.E. 2562 (2019) apply on the personal data protection of Chinese messaging application’s privacy policy and to recommendon how to makesuch privacy policy comply with the PDPA for all intents and purposes. This article will focus mainly on Chinese messaging application (WeChat), who relies heavily on personal data of users and the PDPA, which is enacted to protect the owner of personal data from damages. Therefore, the rights of data subject (App users) will be thoroughly analysed with WeChat Privacy Protection Policy. The prescription of the PDPA and the content of WeChat Privacy Protection Summary are key resources for the analysis. From the study, most WeChat Privacy Protection Policy complies with the PDPA, but the company should adjust its policy to comply with not only General Data Protection Regulation EU 2016/679 (GDPR) but also the PDPA as well. Recommendations are 1 to provide the rights of App users to all current App users internationally instead of limited only to the residents in the European Union, 2 to provide Privacy Policy in Thai language by using simple and straightforward sentences, easy and readable format, and freely accessible, 3 to consider and review own Privacy Policy with other prescription in the PDPA i.e. responsibilities and duties of data controller, data processor, data protection officer.